The Influence of Leadership, Work Environment, and Career Development on Work Achievement: Pengaruh Kepemimpinan, Lingkungan Kerja, dan Pengembangan Karir terhadap Prestasi Kerja - Rozi, Achmad Fatchur; Sumartik, Sumartik (Universitas Muhammadiyah Sidoarjo, 2022)
The Influence of Leadership, Work Environment, and Career Development on Work Achievement of Educational Institutions for Insan Cendekia Mandiri boarding school. This thesis is not published by the Faculty of Economics and Business, Muhammadiyah University of Sidoarjo. This study aims to determine the Influence of Leadership, Work Environment, and Career Development on Work Achievement of Independent Scholar Education Institutions. The analytical tool used is tabulating the questionnaire, collecting data in the form of validity and reliability tests. The hypotheses in this study were tested using classical assumption analysis, multiple linear regression, coefficient of determination (R2), partial correlation coefficient, t test, F test and test using SPSS for Windows version 18 software. The results of this study resulted in several conclusions, namely: ( 1) There is a simultaneous influence of Leadership, Work Environment, and Career Development on Employee Work Performance; (2) There is a partial influence of Leadership, Work Environment, and Career Development on Work Achievement; (3) Among Leadership, Work Environment, and Career Development, Career Development has the most significant effect on employee performance.